(untitled) (Research, Society and Development, 2021)
In this work we present the results of the construction of low-cost equipment for Hall measurements, using the van der Pauw technique. For this, a system was developed composed of an electronic board controlled by a DAQ board that together with software in Labview performs the automation of all necessary measures. The system is capable of carrying out all the necessary switch operations between the contacts to perform the van der Pauw technique and obtain parameters such as electronic mobility, carriers concentration, and electrical resistivities as a function of temperature. Such measures are essential to study the electronic behavior of samples, aiming at their application in electronic devices. To check the behavior of the system, a sample of Indium tin oxide (ITO) was used. In these tests, it was found that the synchronization times used for the measurements show results with low noise and that the assembly allows the carrying out of didactic measures for undergraduate courses and also for research carried out by graduate students.